(untitled) (International Journal of Health, Animal Science and Food Safety, 2016)
Sarconema eurycerca is a common parasitic disease of North America swans and geese. The infection has been correlated with severe heart lesions, often resulting in cardiac failure and death of the animals. Heartworms infections have been previously reported in European swans, and specifically in the United Kingdom and Nederland. Both the countries are characterized by a cold temperate weather, similar to the one that can be found in swan wintering areas of U.S.A. and Canada. The first record of cardiac filariasis associated with Sarconema eurycerca infection in four swans in Italy. Twelve mute swans were examined during avian influenza surveillance activities on migratory birds. Birds were collected in the year 2006, in wintering areas of Eastern Sicily (Italy). Four of the twelve swans showed necrotic-haemorrhagic myocarditis with intra-lesional nematodes. Morphological characteristics identified the parasite as a filarial nematode. Birds lungs samples were used for parasites DNA extraction. The latter was used as template for polymerase chain reaction (PCR) amplification and sequencing of part of the 12S rDNA gene. Comparison of genomic DNA extracted from a reference S. eurycerca isolate confirmed parasite identity and provided the first sequence resources for this species of value to future diagnostic and epidemiological studies.